The Role of Savings Group on the Nutritional and Economic Wellbeing of Rural Households: The Case of World Vision’s Savings for Transformation (S4T) in Zambia - Bwalya, Richard; Zulu, Mabvuto (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Smallholders and the poor populations, especially in rural areas, tend to have little or no access to formal credit, which limits their capacity to invest in the technologies and inputs they need to increase their yields and incomes and reduce hunger and poverty. This mainly arises because financial institutions interested in serving this market face a myriad of risks and challenges associated with agricultural production and lending, including seasonality and the associated irregular cash flows, high transaction costs, and systemic risks, such as floods, droughts, and plant diseases. As a solution to the challenge of financial exclusion among the rural poor, several international development organizations have been using Village Savings and Lending Associations (VSLAs) as an alternative option to increasing financial inclusion among the rural communities in most developing countries. Using both quantitative and qualitative methods, this study aimed to assess whether membership to these VSLAs results in significant improvements in household economic status as well as household food security. The results show that compared to non-members, members of these savings groups are more likely to have increased access to alternative and more sustainable financial tools. Membership to these savings groups is also associated with improved nutrition, education, living standards while the likelihood of being poor is also reduced.